Facile method to synthesize of magnesium-graphene nano sheets for candidate of primary battery electrode - Siburian, Rikson; Paiman, Suriati; Hutagalung, Fajar; Marwan Ali, Ab Malik; Simatupang, Lisnawaty; Goei, Ronn; Rusop, Mohamad Mahmood (Elsevier, 2022)
The effect of particle sizes of Mg on Magnesium-Graphene nano sheets (Mg-GNS (C-π)) interaction when used as an anode of primary battery was evaluated. GNS was synthesized using the modified Hummers method, while Mg/GNS composite with 10–40% Mg was prepared by a facile impregnation method. XRD data of Mg/GNS shows peaks of C(002) and Mg(102) at 2θ = 26.77° and 44.69°, respectively, indicating Mg metals were successfully introduced onto GNS surfaces. These data are consistent with the EDX spectrum which shows peaks of C (0.277 keV) and Mg (1.253 keV). Mg 10%/GNS (3.871 μm) and Mg 30%/GNS (4.485 μm) have the smallest and largest metal particle size deposited, respectively. Mg 10%/GNS (62.9 μS/cm2) has a higher electrical conductivity value than the bare GNS (61.4 μS/cm2) and commercial primary battery anode (Zn plate, 35 μS/cm2). The results obtained show that GNS is able to modify the metallic character of Mg (p-s interaction). Furthermore, the presence of Mg metal deposition on the GNS surface is able to produce Mg/GNS with increased electrical conductivity so that it could be used as an alternative anode primary battery.